Permanent ocular remodeling in the setting of chronic hypotony after trabeculectomy: A case report - Nathaniel Cameron; Taylor Nayman; Sanjay V. Patel; Gavin W. Roddy (American Journal of Ophthalmology Case Reports, 2024)
Purpose: Trabeculectomy surgery is a commonly performed procedure for treatment of glaucoma. While the goal is to lower intraocular pressure, over-filtration may cause hypotony with ocular structural changes and vision loss. Observations: A 53-year-old woman with primary open-angle glaucoma was referred to our service for further evaluation. The patient previously underwent trabeculectomy 9 years prior and was found to have a cataract and hypotony maculopathy in the right eye. Treatment options included cataract surgery alone, bleb revision alone, or combined cataract extraction and bleb revision. Biometry revealed corneal astigmatism in the right eye, and significant disparity in axial length between the two eyes. Since the axial length and corneal astigmatic changes were presumed to be at least partially reversible, measurements from the non-operative left eye influenced the lens selection for the hypotonous right eye. The patient underwent combined phacoemulsification and bleb revision. While IOP increased and hypotony was partly reversed, there was hyperopic and astigmatic refractive surprise after surgery.The patient subsequently underwent intraocular lens exchange using biometric values of the previously hypotonous eye and met the target post-operative refractive goal. Conclusions and importance: This case demonstrates changes to the axial length and ocular structure following longstanding hypotony maculopathy may be permanent, even after restoration of normotensive intraocular pressure.